IMPROVING OUTSOURCING SYSTEM IN INDONESIA: FIXING THE GAP OF LABOUR REGULATION - Nabiyla Risfa Izzati (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2017)
AbstractOutsourcing is always been one crucial issues in Indonesian labour law. Since this system legalized by Law Number 13 Year 2003 on Manpower, there has been a lot of resistance from workers and unions, because outsourcing system is considered detrimental to the position of workers. However, does abolishing outsourcing system the best solution? This research will trace the history of Indonesia's outsourcing system, the advantages and disadvantages of this system, and some possible ways to improve the system. By improving outsourcing system within the legal framework and its implementation, it is not impossible that this system will bring benefits to both workers and employers.  Intisari Outsourcing atau alih daya merupakan salah satu permasalahan yang krusial dalam ranah hukum ketenagakerjaan di Indonesia. Sejak awal model hubungan kerja ini dilegalkan oleh Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan, muncul banyak perlawanan dan resistensi dari kalangan pekerja dan serikat pekerja karena dianggap merugikan posisi pekerja. Namun, apakah menghapuskan sistem outsourcing merupakan solusi? Penelitian ini akan menelusuri sejarah sistem outsourcing Indonesia, kelamahan dan kelebihan sistem ini, serta cara yang mungkin dilakukan untuk memperbaiki sistem ini. Dengan memperbaiki sistem outsourcing dalam kerangka hukum dan pelaksanaan, bukan tidak mungkin sistem ini justru membawa kemanfaatan bagi pekerja maupun pengusaha.